Waterfall-inhabiting Naucoridae (Hemiptera: Heteroptera) of southern India and Sri Lanka: Pogonocaudina Sites and Zettel, n. gen., and a review of Diaphorocoris with descriptions of two new species - Sites, Robert W.; Zettel, Herbert; Arunachalam, M. (Zootaxa, 2011)
A new genus of Naucoridae inhabiting a waterfall in Tamil Nadu state in southern India is described. Pogonocaudina Sites and Zettel NEW GENUS is diagnosed by a dense fringe of long hairs around the perimeter of the posterior abdominal segments, and by both males and females with a single segmented front tarsus with two pretarsal claws. Despite the lack of sexual dimorphism in the forelegs, this new genus is a member of the subfamily Laccocorinae, an assignment based on other characters consistent with this subfamily. Character states of this genus are compared with those of other Asian genera of Laccocorinae. The genus Diaphorocoris is reviewed and two new species are described here: Diaphorocoris arunachalami Sites and Zettel NEW SPECIES and D. kiliyur Sites and Zettel NEW SPECIES. Three species of Diaphorocoris are now known from southern India, and with one other species from Sri Lanka, a total of four species are now known in the genus. A taxonomic key is provided to distinguish all known waterfall-inhabiting Naucoridae in southern India and Sri Lanka.